The influence of nutritional intake on nutritional status of adults admitted to Liver Transplant Service - Zaina, Francisca E; Lopes, Reginaldo W; Tiemann, Layza; Mello, Alessandra (Brazilian Journal of Transplantation, 2004)
Objective: To determine the influence of dietetic intake on nutricional status in adult candidates to orthotopic liver transplant (pre-transplant) and after the procedure (post-transplant). Methods: this prospective study evaluated 48 adults (81.3%) pre-transplant with a mean age of 46.36 years and 18.7 % of transplanted ones, with a mean age of 51.89 years, on admission in the hospital and on the day of discharge. “T” Student test was adopted. The variables studied were gender, age, body mass index, adequacy of current body weight for usual body weight and for ideal body weight, tricipital skin-fold, mid-upper arm muscle circumference, % generalized adipose reserve and nutritional intake control vs. nutritional requirements. Results: In terms of body mass index 51.28% of pre- transplant patients were eutrophic both on admission and discharge and 44.44% of post-transplant patients were overweight on admission and 44.44% were eutrophic on discharge. Some degree of depletion for adequacy of tricipital skin-fold occurred in pre-transplant in patients in 58.96% of in patients and 61.52% on discharge and 44.44% on admission and 66.66% on discharge for Post-transplant patients. Concerning adequacy of mid-upper arm muscle circumference there was not significant incidence of depletion in both periods; 95.83% of them did not reach energy requirements and 85.41 protein requirements due to fasting, low acceptance of hospital diet and hospital discharge. The statistical analysis of anthropometric data showed significant difference between adequacy of current body weight/ideal body weight (p=0.01) in the pre-transplant group as well adequacy of tricipital skin-fold in the post-transplant group (p=0.03). Conclusion: The nutritional requirements might have been overestimated.